HUBUNGAN TINGKAT KESEGARAN JASMANI (PHYSICAL FITNESS) DAN KESEHATAN MENTAL (MENTAL HEALTH) DENGAN PRESTASI BELAJAR PENDIDIKAN JASMANI (PENJAS) - Yusuf, Rusdiana (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Physical fitness and mental health are normal or healthy persons with a healthy mentality that is relatively close to the physical intregity and ideal soul, which is a division of the two elements only between the body and the soul and this is very closely in the student’s learning achievement. This research has purpose to know the relation between level of physical Fitness and mental health with learning achievement of physical education. The method used in this study is the method of analysis and data analysis using linear regression analysis using SPPS 17. The results of research where f arithmetic (58.549)> F table with significant 0.05 ie (3.39) and significant values seen in the column sig ie 0.000Â meansÂ probability 0.000 lessÂ value Â 0.05 Â So that there isÂ no correlational of physical fitness level (physical health) and mental health with learning achievement of Physical Education in "Reject" besides T count (4.893)> from T Table (2.057). Which means there is a significant correlational between the level of physical fitness (physical fitness) and mental health with learning achievement Physical Education